Postmortem Conception: Analyzing Jurisprudence and Ethics in Modern Reproductive Technology - Maya Broke; Faisal Arifin; Ayu Kartini (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2022)
This research examines the use of modern reproductive technology, especially artificial insemination with the sperm of a deceased husband, from the perspective of Islamic law and ethics. By adopting a jurisprudential and ethical approach, this research analyzes the views of ulama as well as relevant sharia postulates regarding the halal and ethical implications of this procedure. The results of the research show that the majority of ulama agree that artificial insemination with the sperm of a deceased husband is haram because it breaks the legal marriage bond and disrupts the clarity of the child's lineage. Children born from this procedure cannot be assigned to their biological father, which has a significant impact on their inheritance rights and social identity. This research also highlights the importance of social and psychological support for children born through this procedure to ensure their long-term well-being. This research recommends that fatwa institutions and religious authorities provide clear guidance regarding the use of reproductive technology in Islam to ensure its conformity with sharia.